Comparison of three EMG-based muscle fatigue assessments in dynamic contractions - Özgören, N. S.; Antan, S. (ISBS Proceedings Archive (Michigan), 2017)
The aim of this study was to (1) focus on the number of peaks methods (NoP) as an alternative method for electromyography (EMG) analysis and to (2) compare the performance of this method with two traditional EMG parameters, mean frequency (MNF) and median frequency (MDF) in assessment of muscle fatigue during cyclic dynamic contractions. A total of 6 participants performed 50 repeated, maximal concentric isokinetic muscle actions of the left leg extensors at a velocity of 180 deg/s using an isokinetic dynamometer. Quantification of the EMG activity of the muscles at each repetition was made by using three methods. NoP values were found to be positively correlated with the peak torque as well as MNF, and MDF. The study showed that the NoP method which has a simple implementation, can be used for assessing the level of muscle fatigue.